Upaya Meningkatkan Hasil Belajar Roll depan senam lantai dengan menggunakan gerakan variasi model Siswa Kelas V UPT SD Negeri 12 Turatea - Bachri, Syamsul; Khalid Rijaluddin; Andi Temassonge (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This research aims to determine the improvement in the learning outcomes of the forward roll (roll depan) floor exercise among fifth-grade students at UPT SD Negeri 12 Turatea through the use of a movement variation model. The type of research used was Classroom Action Research (CAR), conducted in collaboration between the researcher and the teacher, and implemented in two cycles. The research subjects were 23 fifth-grade students at UPT SD Negeri 12 Turatea.The movement variation model applied included forward roll games with a running start, forward roll games with a rope obstacle, and forward roll games with a cardboard box jump start.The research results showed a significant increase from Cycle I to Cycle II. The average student activity increased from 47.5% (sufficient criteria) in Cycle I to 82.5% (good criteria) in Cycle II. The students' classical learning mastery also increased drastically, rising from 65.21% (15 students passed) in Cycle I to 87% (20 students passed) in Cycle II. This increase met the desired minimum mastery target. Thus, it is concluded that learning the forward roll floor exercise through the game model can improve student learning outcomes